SOSIALISASI DETEKSI DINI PENYAKIT TIDAK MENULAR (DD-PTM) DALAM PENCEGAHAN KOMPLIKASI DIABETES MELLITUS DI KELURAHAN BULUSTALAN KECAMATAN SEMARANG SELATAN - Ainnur Rahmanti; Mimin Indah L (JURNAL PENGABDIAN KEPADA MASYARAKAT SISTHANA, 2021)
Background The Healthy Living Community Movement (GERMAS) is a program launched by the Ministry of Health to reduce the main risks of communicable and non-communicable diseases (PTM), especially through nutritional interventions for the first 1000 days of life, improving balanced nutrition consumption patterns for the whole family, increasing regular and measurable physical activity. , improve a healthy lifestyle, improve a healthy environment and reduce cigarette and alcohol consumption. Purpose is to improve the health status of the community through early detection of non-communicable diseases (DD-PTM), especially those with diabetes mellitus. Method begins with interviews with health cadres in the Bulustalan village area, followed by early detection programs and fitness exercises. Results:. Result The health checks carried out were anthropometric measurements in the form of height, weight, abdominal circumference, blood pressure measurements and temporary blood sugar measurements. Of the 50 residents who participated in the DD-PTM implementation, as many as 24% of the residents (12 people) just found out that they had pre-diabetes mellitus, 16% (8 people) already knew that they had hypertension and diabetes mellitus, as many as 6% (3 people) ) had an abdominal circumference of more than 100 cm, 54% (27 people) were in good health. Conclusion: Early detection of non-communicable diseases is very important to prevent further complications. Keywords: